Adult education and the cross-cultural transfer of innovation: A curricular analysis of the rural organization development project in Niger - Peter A. Easton; Maman S. Sidikou (Adult Education Research Conference, 1994)
Careful examination of the "curricular viability" of a new USAID-supported cooperative development strategy in the Republic of Niger provides a key complement to standard forms of development intervention assessment.